Academic-practice partnerships in evidence-based nursing practice: a scoping review protocol. Issue 9 (22nd September 2022) - Halili, Xirongguli; Välimäki, Maritta; Li, Zeen; Tang, Siyuan; Wang, Honghong; Chen, Qirong
Abstract : Introduction: Academic-practice partnerships are a promising strategy that could strengthen the promotion and innovation of evidence-based nursing practice (EBNP). However, there is little evidence of how academic and clinical institutions and individuals should collaborate in each process of EBNP and the factors that influence academic-practice partnerships in EBNP. There is a pressing need to explore the extent of the literature on academic-practice partnerships in EBNP, as well as to classify, compare and summarise the results or opinions obtained from various types of literature to identify both existing knowledge and gaps in the research. Methods and analysis: The scoping review will be conducted following the methodological guidelines provided by the JBI. The scoping review will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews checklist. Seven databases, including the Cochrane Library, PubMed, Web of Science, CINAHL, EMBASE, SCOPUS, Educational Resource Information Center and two Chinese databases (ie, CNKI and WANFANG DATA), will be searched. The grey literature will also be searched using the American Association of Colleges of Nursing, American Nurses Association, Open Grey, Grey Literature Report and the official website of JBI. The literature screening and data extraction will be conducted independently by two researchers. A third researcher will be involved when a consensus is needed. Ethics and dissemination: Ethics approval is not required. The findings of the scoping review will be disseminated in a conference and a peer-reviewed journal.